Sample preparation method for evaluating the ultrasonic C-scan testing effect of composite materials
Through the sample preparation method, standard samples are selected and defects are attached externally, which solves the problem of low sample preparation efficiency and high cost in ultrasonic C scanning detection of composite materials, achieves more efficient and accurate detection results, and improves the reliability of the detection.
Patent Information
- Application Number
- CN202211383637.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-11-07
AI Technical Summary
In the existing ultrasonic C-scan detection of composite materials, defective samples are low in production efficiency, high cost, long periods, and it is difficult to fully reflect the characteristics of composite materials structure, affecting the accuracy and reliability of the detection results.
A sample preparation method is adopted, including selecting standard samples, determining the material, size, location, quantity and laying method of defects, and conducting ultrasonic C scanning detection and file storage. This method considers the material, process and structural characteristics of the composite material, and reflects the characteristics of the actual parts by externally patching defects.
The manufacturing efficiency of ultrasonic C scanning detection of composite materials is improved, the manufacturing cost and cycle are reduced, the accuracy and reliability of the detection results are enhanced, and the detection effect and defect detection ability can be better evaluated.
Smart Images

Figure CN115656329B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nondestructive testing, and in particular to a sample preparation method for evaluating ultrasonic C-scanning testing effects of composite materials. Background Art
[0002] Large composite structures and complex composite materials are currently widely used in many industrial fields. They are very important composite parts with very high quality, cost, safety and performance requirements. In order to ensure the quality of such critical composite structures, ultrasonic C-scanning is usually required to perform 100% non-destructive testing on them. In order to ensure that the ultrasonic C-scanning obtains correct test results, it is necessary to verify the ultrasonic C-scanning test equipment capabilities and the correctness of the ultrasonic C-scanning test process parameters. In order to evaluate the influence of different ultrasonic C-scanning test equipment, test personnel, test processes and test parameters on the test results, the current method is mainly to design and prepare composite comparison test blocks with known defects, and comprehensively judge the correctness and detectability of the ultrasonic C-scanning test results through ultrasonic C-scanning of the comparison test blocks. Therefore, the design and preparation of the comparison test blocks is very important. The difference between the comparison test blocks and the actual composite parts being tested directly affects the detectability of the ultrasonic C-scanning and the correctness of the test results. The current technical practice is to design and prepare simple and small-sized composite comparison test blocks according to the material, process and structural characteristics of the composite parts being tested, and place several representative films inside the comparison as simulated defects to assess the detection adaptability and defect detection capability of the ultrasonic C-scanning.
[0003] At present, when conducting ultrasonic C-scan testing of composite materials, it is usually necessary to prepare defective comparison test blocks based on the material, process, and structural characteristics of the composite structure being tested, in order to evaluate the rationality and correctness of the selected ultrasonic C-scan equipment, process, and testing parameters. The existing defective specimens and their defect simulation methods select materials and processes consistent with the composite parts being tested, manufacture typical simple-shaped small-sized defective test blocks, and place thin film simulated defects at different positions inside the defective test blocks as ultrasonic C-scan comparison test blocks. The significant shortcomings are: (1) Typical simple-shaped small-sized comparison test blocks cannot reflect the geometric characteristics and process characteristics of the composite parts being tested. , thus affecting the true evaluation of the defect detection capability of ultrasonic C-scanning and the correctness and adaptability of the test results; (2) For complex composite materials, it is difficult to reflect the characteristics of actual composite parts through typical simple shape small-size comparison test blocks, thus affecting the judgment of the effectiveness and correctness of ultrasonic C-scanning detection; (3) In the preparation process of traditional typical simple shape small-size defect test blocks, it is necessary to place the material used to simulate the defect inside the sample, which requires a certain production cycle, manufacturing cost, poor defect visualization effect, and is prone to errors beyond expectations; (4) The defect detection probability and the global difference between the comparison test block and the tested part are not considered at the same time. As an improvement to the typical simple shape small-size defect comparison test block, for extremely complex composite parts, when it is difficult to reflect the characteristics of the actual part through the typical simple shape small-size defect test block, there is also a defect simulation method of attaching acoustic attenuation material to the surface of the tested part. Its main shortcomings are: the defect simulation method of external acoustic attenuation materials currently used does not fully consider the process characteristics, structural complexity and ultrasonic C-scan process of the inspected parts, as well as the requirements for defect detection probability and confidence, and does not provide criteria for selecting comparison test blocks and the number of external defects, which affects the evaluation of the comprehensive effect of ultrasonic C-scan detection and the correctness of the detection results, and further affects the reliability of ultrasonic C-scan detection. As an improvement in the defect detection probability, some comparison test blocks have also introduced a method that reflects the defect detection probability, but its main shortcomings are: (1) It does not fully consider the global feature differences between the comparison test blocks and the inspected composite parts; (2) It still uses the preparation method of implanting internal defects, which has high manufacturing costs, low manufacturing efficiency, long manufacturing cycle, and is prone to defect deviation. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] The embodiment of the present invention provides a sample preparation method for evaluating the ultrasonic C-scan detection effect of composite materials, which is used to evaluate the comprehensive detection effect, defect detection capability and detection accuracy of ultrasonic C-scan of composite material structures in a full range, and solves the related technical problems of low manufacturing efficiency, high manufacturing cost and long manufacturing cycle of standard samples of composite materials.
[0006] (II) Technical solution
[0007] An embodiment of the present invention proposes a sample preparation method for evaluating the ultrasonic C-scan detection effect of composite materials, which is characterized by comprising the steps of: selecting a standard sample; preparing defects, including determining the material, size, position, quantity and paving method of the defects; testing the standard sample; and archiving.
[0008] Furthermore, the selection of standard samples includes: according to the actual composite material parts to be tested, the ultrasonic testing test satisfies the calculation formula: Among them, k m is the material factor, k t is the process factor, k s is the structure factor; ΔdB m ΔdB is the change in the amplitude of the ultrasonic signal due to the different materials in the composite material being tested when other conditions remain unchanged, determined by the ultrasonic C-scan test; t ΔdB is the change in the amplitude of the ultrasonic signal due to the different molding processes in the composite material product under test when other conditions remain unchanged, determined by the ultrasonic C-scan test; s k is the dB change in the ultrasonic signal amplitude caused by the different shapes, thicknesses and geometric features of the composite material being tested when other conditions remain unchanged, determined by the ultrasonic C-scan test; m ≥k T When k is , the influence of the material change of the tested composite material on the ultrasonic C-scan is ignored when selecting the standard sample; t ≥k T When k is , the influence of process changes of the tested composite material parts on ultrasonic C scanning is ignored when selecting the standard sample; s ≥k T When k is selected as the standard sample, the influence of the structural geometric characteristics of the tested composite material part on the ultrasonic C-scan is ignored; T It is a constant, and its value range is 0.1 to 0.5, which is determined through experiments according to the requirements of ultrasonic C-scan detection.
[0009] Furthermore, determining the material of the defect includes: selecting a film that does not pollute the surface of the inspected composite material and is easily attached to the surface as the defect preparation material.
[0010] Further, determining the size of the defect includes: determining the size of the defect according to the quality control and inspection requirements of the inspected composite material part
[0011] Further, determining the location of the defect includes: selecting the distribution location of the external defects according to the material, process and geometric structure characteristics of the inspected composite material structure, the external defects are respectively located on the left surface and the right surface of the inspected composite material part, and the number of external defects N on the left surface and the right surface is ab and M ij There is no overlap in the thickness direction of the inspected composite material part, a = 1, 2, ..., n, n is the maximum number of external defect rows on the left surface, b = 1, 2, ..., k, k is the maximum number of external defect columns on the left surface, i = 1, 2, ..., m, m is the maximum number of external defect rows on the right surface, j = 1, 2, ..., q, q is the maximum number of external defect columns on the right surface, select according to the actual situation of the inspected composite material part: N ab =M ij or N ab ≠M ij .
[0012] Further, determining the number of defects includes: determining the number of external defects according to the confidence level and detection probability of the defects, and the calculation formula is: N nk +M mq ≥N p , where N p It is the minimum number of defects under given ultrasonic C-scan defect detection confidence CL and detection probability POD conditions, which is determined by the quality control and inspection requirements of the inspected composite material parts.
[0013] Furthermore, the method of determining the paving of defects includes: according to the determined defect positions and defect quantities, defects of selected sizes are respectively pasted on the left surface and the right surface of the inspected composite material part.
[0014] Furthermore, testing the standard sample includes: performing visual and ultrasonic C-scan testing on the standard sample, and performing positional offset processing on the defects that overlap in the thickness direction on the left and right sides until all defects do not overlap in the thickness direction of the standard sample.
[0015] Furthermore, the materials of the standard samples include composite materials of different resin matrices and ceramic matrices, the preparation processes of the standard samples include autoclave molding and liquid molding processes, and the structures of the standard samples include a combination of one or more structural forms including laminated structure, braided structure, woven structure, sandwich structure, and adhesive structure.
[0016] (III) Beneficial effects
[0017] In summary, the present invention fully considers the characteristics of automatic ultrasonic C-scan detection of composite materials and the probability of defect detection as well as all the characteristics of the actual tested parts. It does not need to separately process defective samples for ultrasonic C-scan detection of composite materials. It can be reused and can fully reflect the influence of the material, process and structural characteristics of the tested composite material structure on the ultrasonic C-scan detection results. It has low cost, short cycle, extremely high preparation efficiency, extremely low labor intensity, and is environmentally friendly. It can better evaluate the effectiveness and correctness of the ultrasonic C-scan detection results of composite materials, and is more conducive to improving the accuracy and reliability of the ultrasonic C-scan detection results. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments of the present invention are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 It is a schematic flow chart of a sample preparation method for evaluating the ultrasonic C-scan detection effect of composite materials according to an embodiment of the present invention;
[0020] Figure 2 It is a schematic diagram of a composite material part to be tested and its defect distribution in a sample preparation method for evaluating the ultrasonic C-scanning test effect of composite materials according to an embodiment of the present invention;
[0021] In the figure: 1, inspected composite material part; 1A, left side surface; 1B, right side surface. DETAILED DESCRIPTION
[0022] The following is a further detailed description of the embodiments of the present invention in conjunction with the accompanying drawings and examples. The detailed description of the following embodiments and the accompanying drawings are used to exemplarily illustrate the principles of the present invention, but cannot be used to limit the scope of the present invention, that is, the present invention is not limited to the described embodiments, and covers any modification, replacement and improvement of parts, components and connection modes without departing from the spirit of the present invention.
[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0024] Please refer to Figure 1The embodiment of the present invention proposes a sample preparation method for evaluating the ultrasonic C-scan detection effect of composite materials, which is characterized by comprising the steps of: selecting a standard sample; preparing defects, including determining the material, size, position, quantity and laying method of the defects; testing the standard sample; and archiving and storing. The characteristics of the composite material ultrasonic automatic C-scan detection and the probability of defect detection as well as all the characteristics of the actual detected parts are fully considered. There is no need to separately process the defective samples for the ultrasonic C-scan detection of composite materials. The method can be reused and can fully reflect the influence of the material, process and structural characteristics of the detected composite material structure on the ultrasonic C-scan detection results. The method has low cost, short cycle, extremely high preparation efficiency, extremely low labor intensity, and environmental protection. It can better evaluate the effectiveness and correctness of the ultrasonic C-scan detection results of composite materials, and is more conducive to improving the accuracy and reliability of the ultrasonic C-scan detection results.
[0025] In some embodiments, selecting a standard sample includes: according to the actual composite material product to be tested, performing an ultrasonic testing test to satisfy the calculation formula: Among them, k m is the material factor, k t is the process factor, k s is the structure factor; ΔdB m ΔdB is the change in the amplitude of the ultrasonic signal due to the different materials in the composite material being tested when other conditions remain unchanged, determined by the ultrasonic C-scan test; t ΔdB is the change in the amplitude of the ultrasonic signal due to the different molding processes in the composite material product under test when other conditions remain unchanged, determined by the ultrasonic C-scan test; s k is the dB change in the ultrasonic signal amplitude caused by the different shapes, thicknesses and geometric features of the composite material being tested when other conditions remain unchanged, determined by the ultrasonic C-scan test; m ≥k T When k is , the influence of the material change of the tested composite material on the ultrasonic C-scan is ignored when selecting the standard sample; t ≥k T When k is , the influence of process changes of the tested composite material parts on ultrasonic C scanning is ignored when selecting the standard sample; s ≥k T When k is selected as the standard sample, the influence of the structural geometric characteristics of the tested composite material part on the ultrasonic C-scan is ignored; T It is a constant, and its value range is 0.1 to 0.5, which is determined through experiments according to the requirements of ultrasonic C-scan detection.
[0026] In some embodiments, determining the material of the defect includes: selecting a thin film that does not pollute the surface of the inspected composite material piece 1 and is easily attached to the surface thereof as the defect preparation material.
[0027] In some embodiments, determining the size of the defect includes: determining the size of the defect according to the quality control and inspection requirements of the inspected composite material 1
[0028] Please refer to Figure 2 In some embodiments, determining the location of the defect includes: selecting the distribution location of the external defects according to the material, process and geometric structure characteristics of the inspected composite material structure, the external defects are respectively located on the left surface 1A and the right surface 1B of the inspected composite material part 1, and the number of external defects N on the left surface 1A and the right surface 1B is ab and M ij There is no overlap in the thickness direction of the inspected composite material part 1, a = 1, 2, ..., n, n is the maximum number of external defect rows on the left surface 1A, b = 1, 2, ..., k, k is the maximum number of external defect columns on the left surface 1A, i = 1, 2, ..., m, m is the maximum number of external defect rows on the right surface 1B, j = 1, 2, ..., q, q is the maximum number of external defect columns on the right surface 1B, select according to the actual situation of the inspected composite material part 1: N ab =M ij or N ab ≠M ij .
[0029] In some embodiments, determining the number of defects includes: determining the number of external defects according to the confidence level and the detection probability of the defects, and the calculation formula is: N nk +M mq ≥N p , where N p is the minimum number of defects under given ultrasonic C-scan defect detection confidence CL and detection probability POD conditions, which is determined by the quality control and inspection requirements of the inspected composite material part 1.
[0030] In some embodiments, the method of determining the paving of defects includes: according to the determined defect positions and defect quantities, defects of selected sizes are respectively applied to the left surface 1A and the right surface 1B of the inspected composite material piece 1 .
[0031] In some embodiments, testing the standard sample includes: performing visual and ultrasonic C-scan testing on the standard sample, and staggering the defects that overlap in the thickness direction on the left and right sides until all defects do not overlap in the thickness direction of the standard sample.
[0032] In some embodiments, according to the material type of the composite material piece 1 being tested, the material of the standard sample includes different resin matrix and ceramic matrix composite materials; according to the molding process of the composite material piece 1 being tested, the preparation process of the standard sample includes autoclave molding and liquid molding process; according to the structural type of the composite material piece 1 being tested, the structure of the standard sample includes a combination of one or more structural forms including laminated structure, braided structure, woven structure, sandwich structure, and adhesive structure.
[0033] Example:
[0034] 2500mm×1600mm composite wall panels and 1300mm×600mm complex composite parts were selected respectively. 6mm, k m =0.5, k t =0.5, k s =0.5, k T =0.1, 0.2, 0.5, N nk =40,M mq =38,N p =73, after 3 ultrasonic C scans, the number of defects detected is 78. The test results show that the scheme can be used to prepare standard samples for evaluating the ultrasonic C-scanning detection effect of composite materials. The preparation of a 1500mm×600mm-2500mm×1600mm composite material part ultrasonic C-scanning standard sample can be completed in only 3 hours. The preparation cost of the standard sample is very low, the preparation cycle is very short, the preparation efficiency is extremely high, the labor intensity is extremely low, and it is environmentally friendly. It can better evaluate the effectiveness and correctness of the ultrasonic C-scanning detection results of composite materials, which is more conducive to improving the accuracy and reliability of the ultrasonic C-scanning detection results.
[0035] It should be clear that the various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referred to each other, and each embodiment focuses on the differences from other embodiments. The present invention is not limited to the specific steps and structures described above and shown in the figures. In addition, for the sake of brevity, a detailed description of known methods and technologies is omitted here.
[0036] The above is only an embodiment of the present application and is not limited to the present application. For those skilled in the art, the present application may have various changes and variations without departing from the scope of the present invention. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A sample preparation method for evaluating the ultrasonic C-scan detection effect of composite materials, characterized in that: Includes steps: Select standard samples; Preparation defects, including determining the material, size, location, number and laying method of defects; Test standard samples; Create and save files; The selection of standard samples includes: According to the actual composite material parts to be tested, the ultrasonic testing test satisfies the calculation formula: in, is the material factor, is the process factor, is the structure factor; It is the dB change in the amplitude of the ultrasonic signal caused by the different materials in the composite material part being tested when other conditions remain unchanged, determined by the ultrasonic C-scan test; It is the dB change in the amplitude of the ultrasonic signal caused by the different molding processes in the composite material part under test when other conditions remain unchanged, determined by the ultrasonic C-scan test; It is the dB change in the amplitude of the ultrasonic signal caused by the different geometric features of the shape, thickness and other characteristics of the composite material being tested when other conditions remain unchanged, determined by the ultrasonic C-scan test; when When selecting the standard sample, the influence of the material change of the tested composite material part on the ultrasonic C-scan is ignored; when When selecting the standard sample, the influence of the process change of the tested composite material part on the ultrasonic C-scan is ignored; when When selecting the standard sample, the influence of the structural geometric characteristics of the tested composite material part on the ultrasonic C-scan is ignored; in, is a constant, and its value range is 0.1~0.5, which is determined through experiments according to the requirements of ultrasonic C-scan detection; The material for determining the defect includes: selecting a film that does not contaminate the surface of the composite material being inspected and is easily attached to the surface thereof as a defect preparation material; Determining the size of defects includes: Determining the size of defects according to the quality control and inspection requirements of the composite material being inspected ; Determining the location of the defect includes: selecting the distribution location of the external defects according to the material, process and geometric structure characteristics of the inspected composite material structure, the external defects are located on the left surface and the right surface of the inspected composite material part, and the number of external defects on the left surface and the right surface is and There is no overlap in the thickness direction of the composite material being tested. , is the maximum number of external defect rows on the left surface, , is the maximum number of external defect columns on the left surface, , is the maximum number of external defect rows on the right surface, , is the maximum number of external defect columns on the right surface, which is selected according to the actual situation of the composite material being tested: or ; Determining the number of defects includes: determining the number of external defects based on the confidence level and detection probability of the defects, and the calculation formula is: For a given ultrasonic C-scan defect detection confidence and detection probability The minimum number of defects under certain conditions is determined by the quality control and inspection requirements of the composite material being inspected.
2. A sample preparation method for evaluating the ultrasonic C-scan detection effect of composite materials according to claim 1, characterized in that: The method of determining the defects includes: according to the determined defect positions and defect quantities, defects of selected sizes are respectively attached to the left surface and the right surface of the inspected composite material part.
3. A sample preparation method for evaluating the ultrasonic C-scan detection effect of composite materials according to claim 2, characterized in that: Testing of the standard sample includes: visual inspection and ultrasonic C-scan inspection of the standard sample, and positional offset processing of overlapping defects in the thickness direction on the left and right sides until all defects do not overlap in the thickness direction of the standard sample.
4. A sample preparation method for evaluating the ultrasonic C-scan detection effect of composite materials according to any one of claims 1 to 3, characterized in that: The materials of standard samples include composite materials with different resin matrices and ceramic matrices. The preparation processes of standard samples include autoclave molding and liquid molding processes. The structures of standard samples include a combination of one or more structural forms including laminated structure, braided structure, woven structure, sandwich structure and adhesive structure.
Citation Information
Patent Citations
Lamination defect evaluation method for drilling of carbon fiber reinforced composite unidirectional laminate
CN105738382A
Method for evaluating ultrasonic detection probability of defects of composite material laminated structure
CN108226291A